2022
DOI: 10.1186/s12944-022-01732-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of novel atherogenicity indices and insulin resistance surrogate markers in predicting the risk of coronary artery disease: a case‒control investigation with comparison to traditional biomarkers

Abstract: Background Due to the contribution of coronary artery disease (CAD) to serious cardiovascular events, determining biomarkers that could robustly predict its risk would be of utmost importance. Thus, this research was designed to assess the value of traditional cardio-metabolic indices, and more novel atherogenicity indices and insulin resistance surrogate markers in the identification of individuals at risk of CAD. Methods A case‒control survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Nevertheless, Spetko et al found in a cross-sectional study that higher levels of ePWV as an indicator of arterial stiffness were associated with poorer left ventricular diastolic function [41]. In a casecontrol study, AIP and TyG index helped to predict CVD risk compared to traditional measures [42]. Karadeniz et al also found that a higher TyG index was strongly 9 Mediators of Inflammation associated with major cardiovascular adverse events [43].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Spetko et al found in a cross-sectional study that higher levels of ePWV as an indicator of arterial stiffness were associated with poorer left ventricular diastolic function [41]. In a casecontrol study, AIP and TyG index helped to predict CVD risk compared to traditional measures [42]. Karadeniz et al also found that a higher TyG index was strongly 9 Mediators of Inflammation associated with major cardiovascular adverse events [43].…”
Section: Discussionmentioning
confidence: 99%
“…The Castelli Risk Index (CRI-I and CRI-II) provides more comprehensive cholesterol metabolism information by incorporating cholesterol levels. An observational study found a signi cant association, indicating a 1.5fold increase in CAD risk with higher CRI, and a notable 2% increase in CAD risk with elevated LCI levels (19). Furthermore, in a study conducted by Li et al, a signi cant correlation was observed between LCI, CRI, and the severity of coronary artery disease (20).…”
Section: Discussionmentioning
confidence: 95%
“…However, the reliance on self-reported outcomes in NHANES study raises concerns about misclassi cation. Furthermore, research by Mahdavi-Roshan et al in Iran, employing a case-control approach, indicated that the TyG-index was more closely associated with CAD risk than either the METS-IR or TyG-BMI [23]. It is crucial to be cautious when interpreting these results because of inherent biases, differing ndings among various studies, dependence on cross-sectional data, and reliance on traditional statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of triglycerides to high-density lipoprotein cholesterol (TG/HDL-C), triglyceride-glucose index (TyG index), TyGindex with body mass index (TyG-BMI), TyG index with waist circumference (TyG-WC), and metabolic score for insulin resistance (METS-IR), are the most common of these less complicated and practical markers [19,20]. Although prior studies have shown associations between these indices and CAD, there is no speci c threshold for utilizing these indices, and it remains uncertain which one of them better predicts CAD [21][22][23].…”
Section: Introductionmentioning
confidence: 99%